E-lestari software / Aidatul Syamimi Mohd Tajudin, Nur Sharmila Sabri and Nurul Ayuni Mohd Azmi - Mohd Tajudin, Aidatul Syamimi; Sabri, Nur Sharmila; Mohd Azmi, Nurul Ayuni (2018)
After initial observation towards the students needed for accommodation, the team had chosen a product that we believe can contribute to the UiTM student. The product is E Booking College. Nowadays, students are very busy with their assignments and social life, therefore they did not have much time to fill up manually the hostel form application at the administration office, they also will miss the due date of the applying the hostel. This product is suitable for student who are want to get the accommodation, hence this product also introduced new system about the fee management where uses the concept "First Come First Serve" that give priority to the individual that make fast paid to the college fee. Absolutely, they directly get the conformation booked for the room without any process and waiting for the "Rayuan Kolej".Hostel management software designed for the purpose of Hostel maintenance. Students can maintain room reservations, online booking, record tracking, current status of the room and also Room availability checking and annual maintenance report available.